γδ T cell distribution in the adventitial layer of non-fertile cystic echinococcosis cysts from cattle livers - Stoore, Caroll; Baquedano, María Soledad.; Hidalgo, Christian; Cabello Verrugio, Claudio.; Paredes, Rodolfo (My University, 2025)
Cystic Echinococcosis (CE) is a zoonotic disease caused by Echinococcus granulosus sensu lato, forming cysts in ruminants and humans with major health and economic impacts. The immune response to CE cysts is complex, with fertility linked to the host’s inflammatory reaction. This study examines γδ T cell distribution and role within the adventitial layer of non-fertile CE cysts in cattle, including cases co-infected with the trematode Fasciola hepatica (FH), a known immune response modulator. Using immunohistochemistry and double immunofluorescence, we observed γδ T cells dispersed in the adventitial layer, enriched in inflammatory zones. Co-infected cases (CE + FH+) showed a reduced γδ T cell proportion among CD3+ T cells compared to non-coinfected cases, suggesting an immunoregulatory effect of FH. Our findings align with prior studies showing γδ T cell recruitment in granulomatous diseases in ruminants but reveal that co-infection alters this response. This study provides the first detailed characterization of γδ T cells in cattle CE cysts, emphasizing their potential role in granulomatous immune responses. It highlights the need for further research into mechanisms influencing CE cyst fertility and immune modulation in helminth co-infections, advancing our understanding of host-pathogen interactions and informing disease management strategies.
Keywords: Cystic echinococcosis, Adventitial layer, Gamma-delta lymphocytes, Co-infection